Identification and analysis of differentially expressed (DE) circRNA in epididymis of yak and cattleyak - Li, Chunhai; Yan, Yan; Pan, Cheng; Adjei, Michael; Shahzad, Khuram; Wang, Peng; Pan, Meilan; Li, Kerui; Wang, Ye; Zhao, Wangsheng (Frontiers in Veterinary Science, 2023)
Circular RNAs (circRNAs), as endogenous non-coding RNA with unique closed ring structure exists in almost all species. CircRNA has RNA receptor resistance and longer half-life and is more stable than linear RNA in tissue and circulation. However, knowledge about the differential expression of circRNA in yak and cattleyak epididymal tissue is limited. A total of 1298 circRNAs were identified in the epididymis of yak and cattleyak, of which 137 differentially expressed (DE) circRNAs and the functions of some of them were clarified in this research. Gene Ontology (GO) enrichment analysis suggested that DE circRNAs were mainly related to metabolic process, development process, immune system process, reproductive process, reproduction, biological adhesion and growth. COG classification analysis showed that the DE circRNAs derived genes were mainly related to replication, recombination and repair. KEGG pathway analysis suggested that DE circRNAs were mainly involved in RNA degradation.